The Role of Agriculture in Shaping the Socioeconomic Status of Women farmers in Tando Allahyar: An Empirical Investigation - Ahmed Ali; Dr Parvez Shaikh; Atiq Ur Rehman (Social Science Review Archives, 2025)
Agriculture is the primary occupation in Taluka Jhando Mari, with a majority of the rural population residing in small villages of 25–50 households. Among female respondents, 71% are actively engaged as farmers or farmworkers. The area reflects a balance between traditional joint families (51%) and contemporary nuclear households, highlighting diverse socio-cultural structures. While 17% of women serve as the main breadwinners, most (83%) do not, indicating the persistence of traditional family roles. Medium-sized families are most prevalent, with an average household size of 8.9 members. The majority of women farmers (57%) are aged 31–41, married, and predominantly illiterate (74.2%), showing significant educational disparities compared to men. Crop farming constitutes the primary economic activities, with most women working 3–5 hours daily in agricultural practices. Despite 93% having more than five years of farming experience, only 0.8% are formally skilled, suggesting a gap between practical experience and recognized agricultural expertise. Seasonal wage patterns indicate higher earnings during the Kharif season (53.8%) compared to Rabi (29%), typically ranging from PKR 3,000–5,000. Household expenditures are dominated by healthcare costs (84%) and food (8%), reflecting economic vulnerability. Annual income analysis shows that 41% of households earn PKR 200,000–250,000, with only 2% surpassing PKR 500,000, while 37% report struggling financially. These findings emphasize the need for targeted interventions, including educational programs, skill development, and income diversification strategies, to enhance the socioeconomic status of women farmers and improve resilience and productivity in rural agricultural communities.